Peran Balai Latihan Kerja dalam Meningkatkan Kompetensi Calon Tenaga Kerja dan Implikasinya terhadap Ketahanan Pribadi Siswa (Studi di Balai Besar Pelatihan Vokasi dan Produktivitas Serang, Kota Serang, Provinsi Banten) - Adie Bangga (Universitas Gadjah Mada, 2022)
ABSTRACT This study aimed to (1) analyze the student training process at BBPVP Serang in improving student competence, (2) identify and analyze the factors that cause BBPVP Serang not to be optimal in increasing student competence, (3) formulate and analyze the efforts of BBPVP Serang in improving competence of prospective workers, (4) analyze the implications of the BBPVP Serang student competency improvement program on students' personal resilience. In this study, the theories used are role theory, human capital theory, competency theory, and human development theory.This research approach is descriptive qualitative research with data collection techniques, namely observation, interviews, documentation and literature. The informants in the study were 26 people consisting of the Head, Staff of BBPVP Serang, Instructors, Students, Alumni and Alumni Users of BBPVP Serang. Data analysis used is data collection, data reduction, data presentation, and drawing conclusions.The results of this study indicate (1) BBPVP Serang carrying out the training process has fulfilled the function of the management/training system according to Permenakertrans No. 8/ 2014, (2) Factors that cause BBPVP Serang not to be optimal: Mismatch of BBPVP Serang training with industry needs, Input from training participants who heterogeneous educational background and age, as well as student personality factors, especially from local communities who have low interest and motivation to work; (3) Efforts of BBPVP Serang to overcome obstacles, namely the Synergy of BBPVP Serang with alumni users, more optimal OJT programs, and student competency certification; (4) The improvement of student competence has been proven to have implications for the formation of students' personal resilience, with indicators of students having competence (hardskills & softskills), certification of work competence, having a permanent job and having a fixed income. Recommendations from the results of the research: (1) The role of BBPVP Serang needs to be increased in its training capacity, (2) Central Government and Regional Government of Banten Province need to make regulations that encourage active industrial participation in improving vocational training for the surrounding community, (3) Selection of trainees must be more selective in looking for participants who have a high interest in learning, and are interested in finding work and work anywhere after completing the training, (4) It is necessary to group/mapping the trainees according to their educational background, interest/motivation to learn, and the age of the trainees, and (5) BBPVP Serang has reactivated the Serang BBPVP training alumni network through the Serang BBPVP tracer study.